Fire Your Stock Analyst! : Analyzing Stocks on Your Own. - Domash, Harry (Financial Times/Prentice Hall Pearson Education [distributor], 2002)
In Fire Your Stock Analyst! , San Francisco Chronicle investment columnist Harry Domash presents a start-to-finish approach to stock selection that draws on winning techniques from the world's top money managers, uses readily available information, and is easy to implement. Learn how to select stocks based on value, growth, and momentum strategies; assess valuation, profitability, risk, business plans, management, and upside/downside potential; decide when to sell; and much more. You'll find everything you need to become a more successful - and self-reliant - investor!